DNA Barcoding Primer Design for Species Identification of Skipjack Tuna, Yellowfin Tuna, and Mackerel: Development and Validation of Primers for Genetic Research - Iranawati, Feni; Martilla, Denisa Amevia Putri Ananda; Aliviyanti, Dian; Arifin, Sunanto (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
The DNA barcoding technique is primarily utilized to rapidly identify species, particularly when samples are damaged and cannot be identified accurately through morphological methods. This approach utilizes polymerase chain reaction (PCR) technology to amplify DNA fragments from the targeted species, with its success largely due to the design of the primers employed. The cytochrome c oxidase subunit I (COI) gene, a mitochondrial gene, is frequently targeted in DNA barcoding and has been proven effective in distinguishing species. At Pondokdadap Port, over 90% of the fish caught consist of skipjack tuna, yellowfin tuna, and mackerel (T2C). This study aimed at designing silico DNA barcoding primers for these three species. The successful development of these primers may facilitate the documentation and understanding of the genetic diversity of the species under study, which is crucial for efficient and effective fisheries management. The primer design process applied Primer-BLAST software from the NCBI website, followed by additional testing with OligoAnalyzer. The selected primer pairs were the forward primer 5'-GGCCCATGCCTTCGTAATGA-3' and the reverse primer 5'-GCAGGGTCGAAGAAGGTTGT-3'. These primers successfully amplified the DNA of T2C fish, with PCR results indicating that the optimal annealing temperature for these primers was 55 °C